Liberal naturalism and the scientific image of the world. Issue 5 (28th May 2019) - Macarthur, David
ABSTRACT: This paper distinguishes between the theoretical scientific image (of the posits of the successful sciences) and the practical scientific image (which, besides explanatory posits, includes everything presupposed by the practices of doing science (e.g. scientists, funding agencies, laboratories, chairs and other artifacts, linguistic communication, a just and democratic ethos). The popular idea that there is a conceptual clash between the scientific and manifest images of the world is revealed as largely illusory. From the perspective of a liberal naturalism, the placement problem for 'problematic' entities or truths is not solved but dissolved. Persons, say, are not posits of any explanatory science, but beings acknowledged as rational agencies in second-personal space. Core elements of the manifest image (e.g. persons) are more deeply rooted in our conceptual scheme than any version of the scientific image.